Learn Swift 2 on the Mac For OS X and iOS - Malik, Waqar (Apress : Imprint: Apress, 2015)
If you are an iOS developer or planning to become one, learning Swift 2 is your #1 priority, and this book tells you everything you need to get up to speed, well, swiftly. You'll start with the Swift Playground and an introduction to object-oriented programming so you can immediately see Swift in action. You then learn about all of the key language features like functions and closures, classes, methods, extensions, and how Swift works just as well as Objective-C when it comes to easy memory management with ARC. Finally you'll learn how to use Swift alongside Objective-C as well as with Core Data, and you'll learn how to put all of the pieces together with a health app using Apple's HealthKit framework.